Correlation Between Adiponectin, Tumor Necrosis Factor-alpha, Insulin Resistance and Atherogenic Dyslipidemia in Non Diabetic Central Obese Males - Candra Ninghayu; Andi Wijaya; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Obesity raises the risk for atherosclerotic cardiovascular disease (ASCVD) through many risk factors including atherogenic dyslipidemia. Atherogenic dyslipidemia is characterized by high levels of triglyceride, increased small dense low density lipoprotein particles, and reduced levels of high density lipoprotein cholesterol. The exact mechanisms of central obesity and this atherogenic lipoprotein phenotype (ALP) is not clearly understood. Central obesity is characterized by a state of systemic low grade inflammation and insulin resistance. Adipose tissue has recently been shown to secrete a variety of bioactive peptides, called adipocytokines, that can potentially affect glucose and lipid metabolism. The aim of this study was to observe the role of adiponectin, tumor necrosis factor-α (TNF- α) and insulin resistance in atherogenic dyslipidemia in nondiabetic central obese males.METHODS: This was a cross-sectional study on 75 non-diabetic central obese male subjects (waist circumferences > 90 cm). Adiponectin and TNF-α testing were performed by ELISA; insulin resistance was assessed by the Homeostasis Model Assessment (HOMA) index, triglyceride was assessed by GPO-PAP, HDL cholesterol and small dense LDL were measured by homogenous method. Statistical analysis was done by SPSS for Windows v. 11.5 with a significance level at p < 0.05. The Pearson and Spearman’s Rho correlation coefficient was used to assess the correlation between various anthropometric and biochemical parameters.RESULTS: There were 75 patients aged 38.0±6.3 years, Adiponectin concentration was 3.55±1.38 μg/ml, HOMA index was 2.28±1.63, TNF-α was 12.42±11.25 pg/ml, triglyceride was 185.17±109.00, HDL-cholesterol was 44.15±9.23 mg/dL, small dense LDL 23.22±12.26 mg/dL. This study revealed that there were correlations between adiponectin and triglyceride (r=-0.236, p=0.042), adiponectin and HDL cholesterol (r=0.300, p=0.009), adiponectin and atherogenic dyslipidemia (r=-0.256, p=0.027), whereas there was no correlation between insulin resistance and TNF-α with the atherogenic dyslipidemia.CONCLUSION: Adiponectin might contribute to atherogenic dyslipidemia in central obese non-diabetic males. Advancing our understanding of the function and measurement of adiponectin serum concentration will be useful in clinical diagnosis of obesity related atherogenic dyslipidemia.KEYWORDS: obesity, waist circumference, adiponectin, insulin resistance, TNF-α, atherogenic dyslipidemia